2018
DOI: 10.1136/bcr-2018-224221
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic acidosis in short bowel syndrome: think D-lactic acid acidosis

Abstract: Short bowel syndrome (SBS) is a condition when a person's gastrointestinal function is insufficient to supply the body with essential nutrients and hydration. Patients with SBS suffer from diarrhoea and symptoms of malabsorption such as weight loss, electrolyte disturbances and vitamin deficiencies. Long-term management of this condition can be complicated by the underlying disease, the abnormal bowel function and issues related to treatment like administration of parenteral nutrition and the use of a central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Increased concentrations of L- and especially D-lactate in the lumen of the GIT and subsequent absorption into systemic circulation play an important role in the local and systemic abnormalities observed in calves with diarrhea ( 13 , 39 41 ). In horses with carbohydrate overload ( 30 , 31 ), cattle with ruminal acidosis ( 42 , 43 ) and humans with SBD ( 42 , 43 ), luminal concentrations of D- and L-lactate are increased. These alteration are associated with decrease lactic acid fermentation from both proliferation of lactate-producing bacteria and inhibition of lactate fermenting bacteria because of the availability of carbohydrates ( 30 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased concentrations of L- and especially D-lactate in the lumen of the GIT and subsequent absorption into systemic circulation play an important role in the local and systemic abnormalities observed in calves with diarrhea ( 13 , 39 41 ). In horses with carbohydrate overload ( 30 , 31 ), cattle with ruminal acidosis ( 42 , 43 ) and humans with SBD ( 42 , 43 ), luminal concentrations of D- and L-lactate are increased. These alteration are associated with decrease lactic acid fermentation from both proliferation of lactate-producing bacteria and inhibition of lactate fermenting bacteria because of the availability of carbohydrates ( 30 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Short bowel syndrome often causes various metabolic acid-base disorders, and some cases of alkalosis have been reported [9]. Conversely, severe acidosis has been reported in a hemodialysis patient [4], likely caused by abnormal production of d-lactate [4][5][6]. However, in the present case, we almost totally resected the colon in which d-lactate producing bacteria grows; thus, this mechanism no longer had an effect on metabolic acidosis.…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that metabolic acidosis occurs in hemodialysis patients with short bowel syndrome [4,5]. In addition to the fact that hemodialysis patients usually tend to be acidotic due to the accumulation of non-volatile acids, it seems that there was an overproduction of d-lactate in these cases [4][5][6]. However, to the best of our knowledge, there have been no reports of an alkalotic hemodialysis patient with short bowel syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to L-LA, serum AG in D-LA is lower than the decrease in serum bicarbonate, and can thus be normal. Therefore, D-LA may also result in hyperchloremic metabolic acidosis [1,5,8]. This is due to the inefficient reabsorption of D-lactate by the kidney, caused by the lack of D-lactate-specific receptors in the lumen of the proximal tubule.…”
Section: Discussionmentioning
confidence: 99%